“Somos el Pueblo”: Resilience and Nationalism in Nicaragua’s Political Struggle - Vey, Sophie (Notas de Antropología de las Américas, 2025)
Amidst the tumultuous echoes of “No somos oposición, somos el pueblo”, resonating across Nicaragua’s streets during the April 2018 protests, a nation grappled with a crisis of identity and governance. What began as a grassroots outcry against perceived injustices quickly burgeoned into a nationwide upheaval, triggering a state of emergency that lasted for months, marking the gravest challenge since the Contra War era. At the heart of this crisis lies a clash between the self-proclaimed “Unidad Nacional Azul y Blanco”, dressed in national colors, aiming to free the “patria” from a repressive regime, and, on the other side, the Frente Sandinista de Liberación Nacional (FSLN), which came into power through the 1979 revolution in the name of national sovereignty. This paper analyzes the strategic use of nationalism in shaping the crisis discourse, drawing on the works of Hobsbawm, Smith, and Anderson. It examines how both factions compete to mold the narrative of an authentic “people” through the appropriation of narratives, symbols, and historical figures, as well as the mechanisms employed to embed the national imaginario within the collective consciousness. In doing so, it delineates nuanced typologies of nationalist fervor and their interplay, revealing the complex web of actors navigating the terrain of allegiances and antagonisms. Finally, the paper will assess the movement’s resilience and current status in 2024, providing insights into its lasting impact on Nicaraguan society.